Microencapsulation by pectin for multi-components carriers bearing both hydrophobic and hydrophilic active agents. (15th February 2018) - Noh, Juran; Kim, Jin; Kim, Jin Sic; Chung, Young Soo; Chang, Suk Tai; Park, Juhyun
Highlights: Pectin microcapsules were fabricated using a microfluidic system. Pectin shells enclosing oil droplets were solidified by precipitation and ionic cross-linking. Nanoparticles of a hydrophilic agent were prepared and dispersed in inner oil droplets. A hydrophobic agent was dissolved in the oil droplets. Pectin microcapsules carried both hydrophilic and hydrophobic agents. Abstract: Oil/water microencapsulation by microfluidic systems has been a prominent delivery method to prepare functional microcapsules in the food, cosmetic, and pharmaceutical industries because it is an easy way to control the shape and size of structures and functionalities. We prepared biocompatible and multi-component microcapsules using the precipitation and ionic crosslinking of pectin in a poor solubility environment and with multivalent cations, respectively. When the aqueous solution (including calcium ions and ethanol) in a sheath flow met the flow of a pectin aqueous solution containing oil droplets, ethanol-gelation and ionic cross-linking occurred, enclosing the inner oil phase droplets by solidified pectin shells. Furthermore, the resulting microcapsules stabilized by pectin shells exhibited functionalities using a hydrophobic agent and nanoparticles of a hydrophilic species that were dissolved and dispersed, respectively, in the oil phase.